2018
DOI: 10.1021/acssuschemeng.7b03479
|View full text |Cite
|
Sign up to set email alerts
|

Perforated BaSnO3 Nanorods Exhibiting Enhanced Efficiency in Dye Sensitized Solar Cells

Abstract: Here, we report the synthesis of phase pure perforated porous BaSnO 3 (BSO) nanorods and their application as an alternative photoanode in dye sensitized solar cells (DSSCs). BaSnO 3, synthesized using different amounts of dextran, has been characterized through various physicochemical techniques to understand the effect of dextran in controlling its morphology. The porous morphology of the rod facilitated enhanced N719 dye loading capability within a very short duration of 20 min. The dye adsorption behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…10,19,24,29,33 In our earlier studies, we have demonstrated a better performance for ZnO rods or fiber-like structures of various other photoanode oxide materials as compared to other morphologies. 5,8,3537 Rutile TiO 2 rods exhibit better chemical stability and performance as a stable photoanode in DSSCs. Out of very rare reports describing the hydrothermally processed rutile nanorods, in most of the cases FTO has been used as substrates to grow 1D morphology followed by post treatment with TiCl 4 to achieve better efficiency in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…10,19,24,29,33 In our earlier studies, we have demonstrated a better performance for ZnO rods or fiber-like structures of various other photoanode oxide materials as compared to other morphologies. 5,8,3537 Rutile TiO 2 rods exhibit better chemical stability and performance as a stable photoanode in DSSCs. Out of very rare reports describing the hydrothermally processed rutile nanorods, in most of the cases FTO has been used as substrates to grow 1D morphology followed by post treatment with TiCl 4 to achieve better efficiency in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 and BSO‐based photoanodes were developed by three‐layer deposition of the screen printing method, consisting of an average thickness of 9.2±0.5 μm. BSO consists of faster dye loading time (1 h) than TiO 2 (24 h), which is precedence to prospect BSO as a suitable alternative to TiO 2 [32] …”
Section: Resultsmentioning
confidence: 99%
“…To overcome the drawback of binary oxides such as dye‐metal oxide complex formation at low pH, degraded stability in acidic dye solutions, a prolonged period of dye loading, the idea of introducing ternary oxides as photoanodes were explored. As an emerging ternary oxide, BaSnO 3 (BSO), as photoanodes, has been studied to address the mentioned problems of TiO 2 [32] . Consisting of high electron mobility, faster dye absorption rate, n‐type resistivity, and low visible absorption, BSO becomes a promising alternative photoanode material for DSSC [33] .…”
Section: Introductionmentioning
confidence: 99%
“…All the devices were measured at the respective open circuit voltage of the devices and the magnitude of the alternative signal used was 10 mV. The experimental data were fitted with the Z‐view software (version 3.4d, Scribner Associates, Inc., USA) using appropriate equivalent circuits …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The experimental data were fitted with the Z-view software (version 3.4d, Scribner Associates, Inc., USA) using appropriate equivalent circuits. 25…”
Section: Dssc Characterizationmentioning
confidence: 99%